Investigating the effects of explanatory-based food safety training: A model of domain knowledge theory perspective - Yu, Heyao; Ma, Jing; Liu, Pei; Sirsat, Sujata A. (International journal of hospitality management, 2020)
•EBT significantly influences progress in food safety knowledge.•Domain knowledge mediates the relationship between EBT and food safety knowledge.•Mastery goal-orientation moderates the effects of EBT on food safety knowledge and motivation to learn.•EBT only influences the motivation to learn for food safety handlers who already have a high learning goal-orientation. Food safety training is essential to reducing foodborne illness; however, limited research has investigated the effects of food safety training content on training effectiveness. Therefore, drawing on the model of domain learning theory, the current study examined the influence of explanatory-based training (EBT; i.e., microbiology and epidemiology knowledge introduction) on the effectiveness of food handlers’ training. Adopting a longitudinal between-subject experimental design and multilevel linear modeling, the study showed that food handlers attending EBT demonstrated significant progress in food safety knowledge acquisition and reported high generalization ability, while only food handlers with high levels of mastery goal-orientation showed increased motivation to learn food safety after attending EBT. Additionally, food safety domain knowledge mediates the relationship between EBT and food handlers’ training effectiveness. This study provides theoretical and practical contributions to food safety training literature by explaining the underlying mechanism that operates between domain knowledge and food safety training effectiveness.